FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE PADA PERUSAHAAN HEALTHCARE PERIODE 2019–2021 - Cindy Cindy; Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2026)
This research is to find out how the influence of firm size, volatility, uniqueness, and tangibility on capital structure in healthcare companies listed on the IDX in the period 2019 to 2021. The sample used in this study was purposive sampling with 15 companies as samples. This research analysis uses panel data regression analysis processed using the E-views 12 application. The results of this study show that Firm size has a positive and significant influence on capital structure, volatility has a positive and insignificant influence on capital structure, uniqueness has a negative and insignificant influence on capital structure, tangibility has a positive and significant influence on capital structure. The implications of this research are expected to help financial management to manage the company's capital structure.